An investigation into syntactic and phonological errors in the English conversations spoken by students at Son Ha high school in Quang Ngai province - Nguyễn,Thị Thuận An; Trần Quang Hải (ĐHĐN : ĐHĐN., 2015)
In the recognition of the importance of understanding errors in the progress of students’ learning English, the researcher conducted this study with the aim at investigating the syntactic and phonological errors in the English conversations. The study was carried out among students at Son Ha High School in Quang Ngai Province. Data were mainly collected from recordings and questionnaires. After the investigation, the errors of those two categories were analyzed with the means of error analyses and their possible sources were proposed. The error analysis of the most frequent errors revealed that the sources of those errors will be the interlingual transfer, intralingual transfer and the communication and learning strategies employed by the learners. It was also observed that the same error will be caused by more than one factor; there were many types of errors when the source will be both the interlingual and intraligual transfer. Finally, on the base of the results of the recording and questionnaires, some suggestions will be applied for teaching and learning English in many high schools.
Keywords: investigation into syntactic and phonological errors in the English conversations spoken by students at Son Ha high school in Quang Ngai province; syntactic and phonological errors in the English -- English conversations spoken